2017
DOI: 10.1161/atvbaha.117.309757
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Iron Status on Risk of Coronary Artery Disease

Abstract: This Mendelian randomization study supports the hypothesis that higher iron status reduces CAD risk. These findings may highlight a therapeutic target.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
71
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 83 publications
(81 citation statements)
references
References 41 publications
9
71
1
Order By: Relevance
“…Epidemiologic studies have shown that iron deficiency, a common cause of microcytic anemia, is associated with artificially raised A1C, although underlying mechanisms remain poorly understood ( 8 ). Our genetic findings are consistent with a previous MR study ( 29 ) and a meta-analysis of prospective studies showing an association between higher iron status and lower CAD risk ( 30 ). Three of the five genetic variants used to instrument decreased Hb and MCV reside in or near genes implicated in iron metabolism, HFE-HIST1H2A (two variants) and TMPRSS6 (one variant).…”
Section: Discussionsupporting
confidence: 92%
“…Epidemiologic studies have shown that iron deficiency, a common cause of microcytic anemia, is associated with artificially raised A1C, although underlying mechanisms remain poorly understood ( 8 ). Our genetic findings are consistent with a previous MR study ( 29 ) and a meta-analysis of prospective studies showing an association between higher iron status and lower CAD risk ( 30 ). Three of the five genetic variants used to instrument decreased Hb and MCV reside in or near genes implicated in iron metabolism, HFE-HIST1H2A (two variants) and TMPRSS6 (one variant).…”
Section: Discussionsupporting
confidence: 92%
“…Its effect on cT1 however remained significant even after correcting for liver iron content in sensitivity analyses, making it unlikely that the association was secondary to bias resulting from iron correction when calculating cT1. Previous Mendelian randomisation studies have shown that higher circulating iron may be cardioprotective, 61 possibly through reduced circulating LDL-cholesterol and lower blood pressure. 62 The same mechanisms may explain why the allele associated with lower circulating iron levels is associated with higher cT1.…”
Section: Discussionmentioning
confidence: 99%
“…In a GWAS consisting of 48,972 individuals of European ancestry, the Genetics of Iron Status Consortium identified five single nucleotide polymorphisms (SNP) associated with serum iron and transferrin saturation, six SNPs associated with ferritin and eight SNPs associated with transferrin at the genome-wide significance threshold (p < 5 × 10 −8 ) [13] (Table 1). Among those SNPs, three SNPs (rs1800562 and rs1799945 in HFE and rs855791 in TMPRSS6) showed a robust and consistent association with a systemic iron status and explained the majority of variance for each iron status biomarker [14] and have been used as instrumental variables for iron status in previous MR studies [14][15][16]. The SNPs were uncorrelated (R 2 < 0.01) and explained 3.4%, 7.2%, 6.9% and 0.9% of the variance for serum iron, transferrin, transferrin saturation and ferritin levels, respectively [13].…”
Section: Instrumental Variable Selectionmentioning
confidence: 99%